Improving Quality Islamic Education for Today's Generation - Abu Bakar, Muhammad; Umroh, Khidriyah Amimatul; Hameed, Fatima (At-tadzkir: Islamic Education Journal, 2023)
Islamic religious education is very important for the formation of one's personality. Guidance and direction are religious doctrines designed to make people believe in the existence of God and religion wholeheartedly, comply with religious orders in the form of worship, and have noble morals. Through studying Islamic religious education, the author hopes that someone can have good values in himself so that he can turn them into good behavior in everyday life. In addition, Islamic religious education can also enable a person not to do things that are not allowed in religion. The application of Islamic education is carried out by increasing piety to Allah SWT, and noble character is the embodiment of the faith that is believed by everyone. Therefore, combining happiness and piety in one person will avoid destructive, slanderous, and socially detrimental behavior, and is very dangerous for the unity and integrity of the nation in the future.